Rehabilitation approach and results of using the biofeedback method (GIGER MD device) in children with neurogenic bladder - Cvitkovic-Roic, Andrea; Mikulic, Danijel; Turudic, Daniel; Milosevic, Danko; Roic, Goran; Matijevic, Valentina (Frontiers in Neurology, 2023)
Background: GIGER MD device applies a biofeedback method through stimulated coordinated rhythmic and dynamic movements of the trunk and extremities in an anti-gravity position, thus helping to regain lost motor functions. Methods: In this article, the performance of the GIGER MD device was evaluated in 36 children with neurogenic bladder measuring gait speed, voiding bladder capacity, deviation from the age-adjusted bladder capacity (measured using the Koff scale), and urinary incontinence. Results: Children using the GIGER MD device had an increase in voiding bladder capacity (33.79%, median volume increase of 50 ml) with a subsequent median decrease in median age-adjusted bladder capacity by 45.50% (median deviation before was 36% vs. 16% after treatment). The number of urinary incontinence episodes also reduced by 55.57% (7 to 3 episodes per day), and the 20-meter motor gait speed increased by 14.26% (from 23 to 19 seconds). Conclusion: Children who follow the GIGER MD therapy regularly for a period of 6 months show that CNS functional damage can be significantly improved.